Analisis Model Pengambilan Keputusan Dalam Program Pemberian Suplemen Makanan Pada Anak-Anak Stunting Kota Surabaya - Nathania Chika Aprilia Kristin; Akmal Bhagaskara; Ahmad Zakky Mubarok (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
Stunting in children and toddlers is an urgent health issue in the city of Surabaya, Indonesia. This research aims to develop effective decision-making strategies in tackling stunting in the city. Through a risk factor analysis approach, evaluation of local needs, and cross-sector collaboration, a holistic and sustainable intervention strategy can be formulated. This study highlights the importance of active community involvement, including the role of mothers and families, as well as support from local governments and health institutions. Regular evaluation of program implementation and monitoring of its impact are also the main focus. Surabaya has allocated a special budget, formed a Stunting Reduction Acceleration Team, and designed an integrated recording system. Even though the food supplement program is supported by the pregnant women class, there are still obstacles such as managing a large population and low food availability. The Fishbone model is used to analyze children's nutritional needs and the factors that cause stunting. It is hoped that the results will provide practical guidance for decision makers and stakeholders in designing and implementing effective stunting prevention programs, with the ultimate aim of improving the health and welfare of children in the city of Surabaya.